MICROWAVE-ABSORPTION MEASUREMENTS OF THE ELECTRICAL-CONDUCTIVITY OF SMALL PARTICLES - LIU, CC; NA, BK; WALTERS, AB; VANNICE, MA (BALTZER SCI PUBL BV, 1994)
A microwave absorption technique based on cavity perturbation theory is shown to be applicable for electrical conductivity measurements of both a small, single-crystal particle and finely divided powder samples when sigma values fall in either the low (sigma < 0.1 OMEGA-1 cm-1) or the intermediate (0.1 less-than-or-equal-to sigma less-than-or-equal-to 100 OMEGA-1 cm-1) conductivity region. The results here pertain to semiconductors in the latter region. If the skin depth of the material becomes significantly smaller than the sample dimension parallel to the E-field, an appreciable error can be introduced into the calculated conductivity values; however, this discrepancy is eliminated by correcting for the field attenuation associated with the penetration depth of the microwaves. A modification of this approach utilizing the skin depth allows a first-order correction to be applied to powder samples which results in the accurate measurement of absolute sigma values, and results with doped Si powders are compared to a values obtained from one small single particle using this microwave technique as well as reported DC a values determined with single crystals. The use of this microwave absorption technique with small particles having high surface/volume ratios, such as catalyst supports and oxide catalysts, under controlled environments can provide fundamental information about adsorption and catalytic processes on such semiconductor surfaces. An application to a ZnO powder demonstrates this capability.
Keywords: DOPANT DENSITY RELATIONSHIP; DOPED SILICON; CAVITY; REGIME; ESR